Simulação de cenários como instrumento de apoio para decisões estratégicas do setor público: uma aplicação em uma Prefeitura - Pasqualotto, Bruna (2020)
The objective of this research is the simulation of future scenarios, to assist in decision-making and achievement of the strategic planning of the Palotina City Hall. Therefore, the Rojo Scenario Simulation Model was applied in all five levels: Delphi technique, competitive intelligence, scenario simulation, strategy formulation and elaboration of action plans. The study uses a qualitative, exploratory approach and is characterized as a case study. To obtain the critical variables, interviews were conducted with semi-structured script and questionnaires with four specialists. Subsequently, the level of competitive intelligence was applied through SWOT analysis, which supported the simulation of the scenarios. After that, for each simulated scenario, strategies were formulated to be followed by the organization. Finally, through the strategies it was possible to develop action plans, that is, goals to achieve the objectives outlined. The results of this study aimed to contribute to the strategic decision-making of public sector organizations, through a compilation of information resulting from the process, making managers able to make decisions with agility and assertiveness. In addition, the object of the study, after the application of the model, has a robust strategic planning, with strategies and actions mapped, which facilitates the execution of routine activities in unstable periods. It is concluded that the model of symualção of future scenarios applied allowed a broader view of the leaders in relation to the variables of greater interference in the execution of activities, providing improvement in the processes through the reduction of uncertainties.